EIB Statistical Report 2019 - European Investment Bank (European Investment Bank, 2020)
The Statistical Report presents in list form the projects financed and borrowings undertaken by the EIB in 2019, together with a list of the EIF's projects. It also includes summary tables for the year and over the last five years.